Improved non-singular fast terminal sliding mode PMSM control strategy - Jingbin Yan; Haoxuan Hu (PLoS ONE, 2025)
To strengthen the overall control capability of the permanent magnet synchronous motor (PMSM) system, an improved non-singular fast terminal sliding-mode control strategy is proposed, that can simultaneously improve the shortcomings of traditional PI and sliding mode control (SMC), which include a large overshoot, large jitter, and poor robustness. First, a new type of non-singular fast terminal sliding-mode surface was constructed according to a surface-mounted PMSM, which avoids singular phenomena in the system. An improved power-reaching law was designed, which not only enables the control system to quickly approach the error to zero, but can also better suppress the chattering phenomenon. Moreover, an adaptive law is introduced to regulate the reaching law coefficient in real time, which further increases the control precision. The system stability was proven using the Lyapunov stability theory. Second, a beat-free predictive current controller was designed for the current loop to further strengthen the system's dynamic response. The matching disturbance of the extended state observer (ESO) is subsequently introduced, and the observed value is transmitted to the designed speed controller in real time. The advantages of the proposed strategy were analyzed through simulations, and its reliability was verified experimentally. Finally, through the simulation and experimental results, it was concluded that the improved non-singular fast terminal sliding mode control (INFTSMC) strategy for PMSM systems can overcome the shortcomings of traditional PI and sliding-mode control systems and increase the response speed and anti-interference ability of the system.